Efficient and accurate simulation of the packaging forming process. Issue 8 (27th June 2018) - Robertsson, Kristofer; Borgqvist, Eric; Wallin, Mathias; Ristinmaa, Matti; Tryding, Johan; Giampieri, Andrea; Perego, Umberto
Abstract : To allow for large‐scale forming applications, such as converting paperboard into package containers, efficient and reliable numerical tools are needed. In finite element simulations of thin structures, elements including structural features are required to reduce the computational cost. Solid‐shell elements based on reduced integration with hourglass stabilization is an attractive choice. One advantage of this choice is the natural inclusion of the thickness, not present in standard degenerated shells, which is especially important for many problems involving contact. Furthermore, no restrictions are imposed on the constitutive models since the solid‐shell element does not require the plane stress condition to be enforced. In this work, a recently proposed efficient solid‐shell element is implemented together with a state‐of‐the‐art continuum model for paperboard. This approach is validated by comparing the obtained numerical results with experimental results for paperboard as well as with those found by using 3D continuum elements. To show the potential of this approach, a large‐scale forming simulation of paperboard is used as a proof of concept. Abstract : An approach to simulate the packaging forming process is presented. The approach is based on a state‐of‐the‐art continuum model for paperboard together with a recently proposed efficient solid‐shell element.